Enhanced microscale heat transfer : a numerical investigation with experimental design - Lai, Sze Ming (2015)
Fluid flow in microchannels offer high convective heat transfer coefficients between the fluid and the channel wall, but are seldom utilised due to their high cost. In this report, microscale annuli were created by fitting conventionally machined inserts into a concentric macro pipe. These low cost microchannels and their applications in macro geometry may create significant cost savings by reducing the amount of material and coolant required. Different nature-inspired surface patterns were incorporated onto each insert and a parametric study was performed numerically for pattern height and width variations. The flow rates tested were 1.5 and 4 L/min at the heat rate of 1,000 W, and 5 and 8 L/min at 2,500 W. Of the three profiles, the inverted fish-scale performed best in terms of demonstrating the highest convective heat transfer coefficient, followed by the fish-scale, then the durian – all outperforming the smooth insert. Also, increasing height and decreasing width resulted in a higher convection coefficient but at the expense of pressure loss. These two parameters were benchmarked at 10 kW⁄m2∙K and 300 kPa respectively. The inverted fish-scale at maximum height and minimum width provided the highest convection coefficient of 65.5 kW⁄m2∙K but exceeded the benchmark by 61.7 kPa. Alternatively, fish-scale provided up to 59.9 kW⁄m2∙K at 266.1 kPa. The effects of the enhanced convection coefficient and aggravated pressure loss were both attributed to high turbulence intensity, recirculation and redeveloping boundary layers. The presence of recirculating flows resulted in a smaller effective flow path, thus increasing fluid velocity and heat transfer capabilities. Building upon the previous test rig, this report comprehensively covers the experimental design and setup with equipment selection and modification. A possible future improvement would be to increase the variations of flow rates at lower heat rates to provide a more holistic study.